Cohesive substitution in the Qurʼān - Dror, Yehudit (Lingua Posnaniensis, 2017)
This article describes the use of cohesive substitution in the Qurʼān. In Halliday and Hasan’s model of cohesion, this term refers to the replacement of one syntactic item by another; this article asks several questions in this regard: How is cohesive substitution realized in the Qurʼān? What items does it replace? Why is it used? The study finds that there are only a few cases of cohesive substitution in the Qurʼān, and the nominal and verbal substitution operate in the Qurʼān as they do in English. In that language, the forms one and the same are employed for nominal substitution. In the Qurʼān the forms ʼaḥad “one” (sg. masc.), ʼiḥdā “one” (sg. fem.) and miṯlu ḏālika “the same” can be considered equivalent to the English form one and the same. Verbal substitution in Arabic is realized by the verb yaf’alu “he will do,” “he does” (and is not followed by the anaphoric pronoun ḏālika “that”), replacing only the verb without its complement. No occurrences of clausal substitutions were found because usually variations of anaphoric reference (e.g., ḏālika “that” or ka-ḏālika “like that”) were used instead. From a pragmatic viewpoint, cohesive substitution is used to prevent repetition of the same word found in the immediately preceding clause.